2001
DOI: 10.1364/ol.26.000322
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of angular distributions by use of low-coherence interferometry for light-scattering spectroscopy

Abstract: We present a novel interferometer for measuring angular distributions of backscattered light. The new system exploits a low-coherence source in a modified Michelson interferometer to provide depth resolution, as in optical coherence tomography, but includes an imaging system that permits the angle of the reference field to be varied in the detector plane by simple translation of an optical element. We employ this system to examine the angular distribution of light scattered by polystyrene microspheres. The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 11 publications
0
40
0
Order By: Relevance
“…3). OCT contrast enhancement (prerequisite 3) has been accomplished by introducing polarization-sensitive OCT, [24][25][26][27][28] phasesensitive OCT, [29][30][31][32][33] optical coherence elastography, [34][35][36][37][38][39] spectroscopic low coherence interferometry, [40][41][42][43] elastic scattering spectroscopy, 31,[44][45][46] and nonlinear interferometric vibrational imaging (NIVI), as well as employing endogenous or exogenous contrast. [47][48][49][50][51][52] In this paper, a recently developed contrast improvement for OCT, named label-free optical angiography, is reviewed (cf.…”
Section: Introductionmentioning
confidence: 99%
“…3). OCT contrast enhancement (prerequisite 3) has been accomplished by introducing polarization-sensitive OCT, [24][25][26][27][28] phasesensitive OCT, [29][30][31][32][33] optical coherence elastography, [34][35][36][37][38][39] spectroscopic low coherence interferometry, [40][41][42][43] elastic scattering spectroscopy, 31,[44][45][46] and nonlinear interferometric vibrational imaging (NIVI), as well as employing endogenous or exogenous contrast. [47][48][49][50][51][52] In this paper, a recently developed contrast improvement for OCT, named label-free optical angiography, is reviewed (cf.…”
Section: Introductionmentioning
confidence: 99%
“…The detected signal at pixel (m, n) can be related to the signal and reference fields (E s , E r ) as: (1) where φ is the phase difference between the two fields and 〈...〉 denotes an ensemble average in time. The interference term is extracted by measuring the intensity of the signal and reference beams independently and subtracting them from the total intensity.…”
Section: Theory Of Detected Signalmentioning
confidence: 99%
“…Angle-resolved low coherence interferometry (a/LCI) has been developed as a means to obtain sub-surface structural information by examining the angular distribution of scattered light [1][2][3]. The a/LCI technique combines the ability of low coherence interferometry to detect singly scattered light from sub-surface sites with the capability of light scattering methods to obtain structural information with sub-wavelength precision and accuracy [2,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 More recently, angle-resolved low-coherence interferometry was used to obtain structural information by examination of the angular distribution of scattered light. 8,9 Angle-resolved LCI has been successfully applied to measuring cellular morphology 3 and to diagnosing intraepithelial neoplasia in an animal model of carcinogenesis. 6 The latter study was significant because it demonstrated the strength of joining LSS and LCI as a biomedical diagnostic technique.…”
mentioning
confidence: 99%